The Impact of Women Empowering on Psychosocial Well-Being in Light of Vision 2030 - Amani O. Abuzahera (المجلة الدولية للعلوم الإنسانية والاجتماعية)
This thesis explores the impact of women’s empowerment initiatives under Saudi Arabia's Vision 2030 on their psychosocial well-being. Focusing on the quantitative analysis of survey data, the research investigates the relationship between increased access to education, workforce participation, and leadership roles with improvements in women’s mental health, emotional stability, and self-esteem. The study uses a structured questionnaire to assess women’s perceptions of empowerment in the domains of education, workforce, leadership, and social integration, as well as the barriers they face in these areas.  The findings reveal that while significant positive changes have been observed, particularly in workforce participation and leadership opportunities, the psychosocial benefits, including mental health and self-esteem, are experienced variably across different demographic groups. The data further highlights persistent barriers, such as cultural and economic challenges, that limit the effectiveness of these reforms. This research provides a statistical analysis of the progress made under Vision 2030 and identifies areas where further efforts are needed to achieve full empowerment. The study contributes to the understanding of how national policies can influence women’s psychosocial well-being, offering insights for policymakers to refine initiatives that aim to empower women and promote gender equality in Saudi Arabia.